Solvatochromism, acidochromism and aggregation-induced emission of propeller-shaped spiroborates. Issue 42 (10th October 2018) - Li, Kang; Cui, Jichun; Yang, Zeren; Huo, Yanmin; Duan, Wenzeng; Gong, Shuwen; Liu, Zhipeng
Abstract : Propeller-shaped pyridyl-enolato-catecholate/-salicyl spiroborates (Sborepy1–6 ) were synthesized. Abstract : Propeller-shaped pyridyl-enolato-catecholate/-salicyl spiroborates (Sborepy1–6 ) were synthesized. The complexesSborepy3–6 show weak emission in fluid solution and aggregation-induced emission enhancement in the aggregation state with large Stokes shifts of 4025–5237 cm −1 . Moreover, intense solid-state emissions with high Φ f ranging from 25% to 37% were observed forSborepy3–6 owing to the weak intermolecular interactions in their solid-state. The AIE and intense solid-state emission have been revealed via the X-ray diffraction analysis and theoretical calculations. Furthermore, the solvatochromism in the solution state and the potential application as a fluorescent acidic vapour sensor in the solid state ofSborepy3 andSborepy6 were also demonstrated.